Flat and compact switchable dual wavelength output at 1060nm from ytterbium doped fiber laser with an AWG as a wavelength selector - Ahmad, Harith; Latif, Amirah Abdul; Norizan, Siti Fatimah; Zulkifli, Mohd Zamani; Harun, Sulaiman Wadi (Elsevier, 2011)
A dual-wavelength ytterbium doped fiber laser with a narrowest spacing of 0.53 nm and widest spacing of 12.2 nm at 1064 nm is presented in this paper. An arrayed waveguide grating (AWG) together with an optical channel selector (OCS) have also been incorporated in the proposed setup that works as a switchable mechanism giving 23 different wavelength tunings. Producing an average output power of -8 dB m and side mode suppression ratio (SMSR) of 59.65 dB, this dual-wavelength fiber laser is quite stable with an output power variance as low as 0.47 dB giving it an advantage due to its switching ability and stable dual-wavelength output powers.